Emotion and Devotion : The Meaning of Mary in Medieval Religious Cultures - Rubin, Miri, 1956- (Book collections on Project MUSE., 2009)
In Emotion and Devotion Miri Rubin explores the craft of the historian through a series of studies of medieval religious cultures. In three original chapters she approaches the medieval figure of the Virgin Mary with the aim of unravelling meaning and experience. Hymns and miracle tales, altarpieces and sermons - a wide range of sources from many European regions - are made to reveal the creativity and richness which they elicited in medieval people, women and men, clergy and laity, people of status and riches as well as those of modest means.